Cost of Quality Calculation in an Innovative Strategic Industry: Evidence from the EU Defence Sector - Jolanta DYBEK; Wojciech SADKOWSKI; Anna SŁAWIK (Communications of International Proceedings, 2020)
The research aims to test an original cost of quality (CoQ) calculation in an innovative organisation operating in the European defence industry. Our methodology embraces the identification, classification and estimation of CoQ – based on business process mapping and accounting data exploration – as well as a structure and ratio analysis thereof. The main findings show that CoQ constitutes over 39% of operating costs of the company which is the subject of our study, and they are present in nearly all business processes. We find a very high share of compliance costs (>84% of total CoQ), and only a minor percentage of non-compliance costs (
Keywords: Cost of Quality; Cost Calculation; Defence Industry; Innovative Organisations; Management Accounting.